PENGARUH ATTRACTION, ACCESSIBILITY, AMENITIES, DAN ANCILLARY TERHADAP KEPUASAN PENGUNJUNG PADA WISATA KOPI RIGIS JAYA DI KECAMATAN AIR HITAM, KABUPATEN LAMPUNG BARAT, PROVINSI LAMPUNG - Firman Handika; Suprihatin Ali; Ghia Subagja (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This research aims to explain the influence of attraction, accessibility, amenities, and ancillary on visitor satisfaction atthe Rigis Jaya Coffee Tour in Air Hitam District, West Lampung Regency, Lampung Province. The independent variablesused in this research are attraction (X1), accessibility (X2), amenities (X3), and ancillary (X4) and visitor satisfaction asthe dependent variable. This research uses a quantitative approach with explanatory research. The population in thisstudy were visitors to the Rigis Jaya coffee tourist attraction. The data was obtained from a questionnaire using a Likertscale which was distributed via Google Form to social media, Intragram, WhatsApp and personal chat. The sample inthis study amounted to 100 samples taken using purposive sampling technique. The data in this study were analyzedusing multiple linear regression with simultaneous results of the attraction, accessibility, amenities and ancillaryvariables having a significant effect on the satisfaction of visitors to the Rigis Jaya coffee tourist attraction with an RSquare value of 0.811 or 81.1%. Meanwhile, partial results show that the variables attraction, accessibility, amenities,and ancillary have a significant influence on visitor satisfaction at the Rigis Jaya Coffee Tour in Air Hitam District, WestLampung Regency, Lampung Province. It is hoped that this research can add insight for future researchers, where thisresearch can become a reference for further research in solving problems related to the influence of attraction,accessibility, amenities and ancillary variables on visitor satisfaction at the Rigis Jaya coffee tourism site.